Modified anterior approach preserving Retzius space versus standard anterior approach robot-assisted radical prostatectomy: A matched-pair analysis - Li, Hui; Yang, Chao; Liao, Zhonghong; Wang, Kaihong; Zhang, Yida; Cao, Runfu (Frontiers in Oncology, 2023)
Objective To compare our initial perioperative and postoperative outcomes of the modified anterior approach (MA) with Retzius space preservation robot-assisted radical prostatectomy (RARP) with the standard anterior approach (SA) RARP. Materials and methods A retrospective analysis was performed on 116 patients with RARP completed by the same surgeon between September 2019 and March 2022. They were divided into SA-RARP group (77 cases) and MA-RARP group (39 cases). Propensity score matching was performed using eight preoperative variables, including age, BMI, preoperative PSA, biopsy Gleason score, prostate volume, D’Amico risk classification, SHIM, and clinical T stage. Functional outcome was assessed by urine pad count and SHIM after surgery, and oncological outcome was assessed by statistics of postoperative pathological findings as well as follow-up postoperative PSA. The median follow-up was 13 months and 17 months for MA-RARP and SA-RARP groups respectively. Results Propensity score matching was performed 1:1, and baseline data were comparable between the two groups after matching. Comparison of postoperative data: MA-RARP group had less mean EBL than SA-RARP group (200 vs 150 ml, p = 0.033). PSM did not differ between groups (p = 1). In terms of urinary control recovery, the MA-RARP group showed significant advantages in urinary control recovery at 24 h, 2 weeks, 1 month and 3 months after catheter removal, respectively (48.6% vs 5.7%, p < 0.001; 80% vs 22.9%, p < 0.001; 94.3% vs 51.4%, p < 0.001; 100% vs 74.3%, p = 0.002). This advantage gradually disappeared 6 months or more after surgery. The median time to recovery of sexual function was shorter in the MA-RARP group (165 vs 255 d, p = 0.001). Conclusion MA-RARP is safe and reliable, and can achieve better early urinary control function and sexual function recovery while achieving the primary tumor control goal.